Literature review tabulation: A concept (LR-TAB) / Azizan Zainuddin ... [et al.] - Zainuddin, Azizan; Abd Rahim, Memiyanty; Mohamed Harith, Nor Hafizah; Abd Samad, Suhaimi; Yusof, Radduan (2021)
Most students tend to pick insufficient input and later find it difficult to organize their literature writing. Therefore, they face difficulty in synthesizing, critiquing, and explaining the literature review. Till today, there is little to no studies proving that there is a certain standard to adhere to when writing a literature review. Thus, for students who are still new in the research field, they will face challenges in finding the key points required to be placed in the chapter. Based on a preliminary survey conducted among the postgraduate students of the Faculty of Administrative Science and Policy Studies, 93.6% of them felt that they need a system that can help them to identify the main points required to be put in the literature review section. This is in parallel with the characteristics of the system to be applied in LR-TAB that suits the need of new researchers especially postgraduate students who require a system to facilitate and ease the searching and writing of literature reviews. Due to those reasons, the aim of having LR-TAB is expected to guide new researchers to enhance their searching and reading skills for literature review. The novelty of LR-TAB is that it is very easy to be implemented since it has a friendly search feature and does not require tedious training. The specialty of the LR-TAB is it contains a process of picking the right information to be put in the chapter of literature review within a short time. The impacts of LR-TAB include its ability to assist non-native speakers in writing and understanding the literature review, enhance students’ motivation in writing a literature review, and familiarize the students with the skill in identifying the significant points of the literature. Therefore, it is anticipated that the innovation created will not just act as a guideline but also boost the confidence level of new researchers, specifically postgraduate students in writing their dissertations or thesis.